Cement mixture using waterfall stone powder of Titi Hayun Kedah - Mohd Hafiz Bin Rodzi (School of Manufacturing Engineering, University Malaysia Perlis, 2010)
This project conducted to study whether the mixture concrete with stone from Titi Hayun, Kedah can be done to produce same strength with original strength cement. Normally cement strength is enough already to generate construction in nowadays compared with only used stone solely a long time ago.